Modelling of groundwater pumping scenarios and their impact on saline water intrusion in a Tripoli coastal aquifer, Libya - Elaswed, Nadia Ahmed; Mohammad, Thamer Ahmad; Ghazali, Abdul Halim; Md Yusoff, Zainuddin (Universiti Putra Malaysia Press, 2019)
Tripoli coastal aquifer, Libya, which is located in a densely urbanised area, is the primary source of water supply in Tripoli city. In the last few decades and due to population growth, more than 100 wells have been drilled in Tripoli aquifer for the purpose of increasing pumping to meet demand on groundwater. The urbanisation at the Tripoli upper aquifer system has reduced the recharge rates and affected the groundwater storage. In this study, changes in groundwater dynamics in Tripoli's unconfined aquifers were simulated using MODFLOW-2005 code. The model was calibrated and validated using measured and simulated values. Statistical tests such as coefficient of determination, R2 mean error, mean absolute error, and the root mean square error were computed and found to be 0.97, 0.31, 1.70 and 2.32 respectively. The simulation will assist in the assessment of the long term saline water intrusion. Calibrated transient groundwater flow models for the years 2020 – 2100 indicated that this case is likely to occur along pumping profiles with high pumping rates. Simulation results show that the groundwater levels will decline and exceed 12 m in the Southern area while in the Northern area near the coastal line, depletion is continuous and more than 70 wells will face saline water intrusion by the year 2100. Doubling the pumping rate from the wells will accelerate the drop in the groundwater levels and about 98% of the wells will be subjected to high salinity level by 2100. The salinity levels in these wells will make the groundwater unfit for human consumption.